Beautiful wounds : a search for solace and light in Washington's Channeled Scablands - Connor, Timothy (Journalist) (The Countryman Press, an imprint of W.W. Norton Company, 2022)
"A photographic journey through the origins and mysteries of a natural treasure of the West. In Beautiful Wounds, Northwestern photographic journalist Timothy Connor combines stunning artwork, historical narrative, and personal experience in this love letter to the Channeled Scablands in southeastern Washington state. Carved and scoured by cataclysmic floods over two million years, the region is remarkable for its harsh beauty and diversity of natural features, including cataracts and buttes. Connor's photography captures the rugged landscapes, sweeping horizons, cascading water channels, and vibrant wildlife. The author also examines the ecological origins of the area through the story of J. Harlen Bretz, the geologist who in the 1920s first suggested that massive floods formed the scablands. Combined with the touching story of the author's own journey of grief, Beautiful Wounds is a moving tribute to the healing power of nature and time"--